PENGARUH ASIMETRI INFORMASI, PRAKTIK MEKANISME CORPORATE GOVERNANCE TERHADAP EARNINGS MANAGEMENT DAN NILAI PERUSAHAAN (Studi Pada Perusahaan LQ45) - Rahmani, Nur; Efni, Yulia; Andreas, Andreas (Jurnal Tepak Manajemen Bisnis, 2016)
The purpose of this research is to find out the influence of information asymmetry, mechanism practical Corporate Governance through Earnings Management directly through the value of company and to observe the influence of information asymmetry, mechanism practical Corporate Governance which has mediated by Earnings Management through the value of company directly and indirectly. The population of this research is LQ45 Company which has registered in BEI in 2009- 2013 for 45 companies in LQ45 Company. Sample of this research is measure by using purposive sampling method, and the result is 22 companies as sample. The result of this research proved that information asymmetry has influence significantly through value of company, there is no significant effect between information asymmetry and value of company which has mediated by earnings management, there is no significant effect between corporate governance and company value, there is significant effect between corporate governance which has mediated by earnings management through company value indirectly and there is significant effect between earnings management and company value.